2020
DOI: 10.31234/osf.io/7v5nq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of human-animal interactions on affect and cognition

Abstract: Human-animal interaction has clear positive effects on people's affect and stress. But less is know about how animal interactions influence cognition. The aim of this study is to investigate whether interacting with animals improves cognitive performance, specifically executive functioning. To test this, we conducted two experiments in which we had participants self-report their affect and complete a series of cognitive tasks (long-term memory, attentional control, and working memory) before and after either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Much of the HAI literature to date has focused on how HAI (i.e., dogs) benefits humans' affect and stress (Allen et al, 2001(Allen et al, , 2002Beetz et al, 2012;Crossman et al, 2020;McConnell et al, 2011). Significantly less attention has been given to how interactions with companion animals impact human cognition or other neurological outcomes, particularly in adult samples (Gee et al, 2015a;Gee et al, 2015b;Thayer & Stevens, 2021;Trammell, 2019). However, some investigators hypothesize that HAI (e.g., gazing at pets, directed attention to pets) could promote shortterm cognitive health through enhanced attentional control, working memory, and reduced autonomic responses to stress (Thayer & Stevens, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the HAI literature to date has focused on how HAI (i.e., dogs) benefits humans' affect and stress (Allen et al, 2001(Allen et al, , 2002Beetz et al, 2012;Crossman et al, 2020;McConnell et al, 2011). Significantly less attention has been given to how interactions with companion animals impact human cognition or other neurological outcomes, particularly in adult samples (Gee et al, 2015a;Gee et al, 2015b;Thayer & Stevens, 2021;Trammell, 2019). However, some investigators hypothesize that HAI (e.g., gazing at pets, directed attention to pets) could promote shortterm cognitive health through enhanced attentional control, working memory, and reduced autonomic responses to stress (Thayer & Stevens, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite hypotheses that interactions with companion animals may benefit cognition, short-term studies have found no impact of HAI on select cognitive domains such as working memory (Gee et al, 2015a; Gee et al, 2015b) and long-term memory (e.g., Trammell, 2019). Potential explanations for the lack of observed associations between HAI and cognition have been proposed (Thayer & Stevens, 2021). First, the threshold for the impact of HAI on cognition may be hard to reach using study designs that focus on short-term interactions with unfamiliar (and therefore unbonded) animals (Thayer & Stevens, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations